Effect of feeding high yielding fodders on growth performance of growing Hilly Brown Bengal goat (Bangladesh Journal of Livestock Research, 2021)
This study was carried out to evaluate the feeding effect of high yielding fodders (HYF) on feed intake and growth performance of growing Hilly Brown Bengal (HBB) goat. For this purpose, a feeding trail was conducted with 16 growing HBB kids (4 to 5 months) by dividing equally in four groups having four replicates for a period of 75 days. The goats in group T0 (control) received natural grass along with 101.30g concentrates and adlibitum cowpea hay, whereas in group T1, T2 and T3, only natural grass was replaced by BLRI Napier 3, BLRI Napier 4 and Ruzi fodder, respectively. Total dry matter intake (DMI), roughages DMI, crude protein intake (CP), body weight gain (kg), average daily gain (g) and forth night body weight gain (g/day) were studied. Results revealed that, DMI (288.39, 285.71, 293.48 and 301.35 g/day in group T0, T1, T2 and T3, respectively), body weight gain (3.60, 3.74, 3.73 and 3.77 kg in group T0, T1, T2 and T3, respectively), average daily gain (47.32, 49.16, 49.12 and 48.92 g in group T0, T1, T2 and T3, respectively) and feed conversion ratio (6.2, 5.9, 6.0 and 6.1 in group T0, T1, T2 and T3, respectively) of HBB kids were not differed significantly (P>0.05) for all the treatment groups. The DMI from roughages (196.2, 193.5, 201.3 and 209.2 g/day in group T0, T1, T2 and T3, respectively) and CP intake (38.7, 42.1, 48.3 and 38.8 g/day in group T0, T1, T2 and T3, respectively) were significantly varied (P0.05) gained with feeding of HYF for all the treatment groups. From this study, it can be concluded that, growing HBB kids could equally be supplied with either BLRI Napier 3 or BLRI Napier 4 or Ruzi fodder in addition to ad libitum cowpea hay for better voluntary feed intake and growth.Bang. J. Livs. Res. Vol. 27 (1&2), 2020: P. 73-81